Analysis and Design of Information Systems for Make-Up Using the Waterfall Methodology - Namy Raptama; Riki (bit-Tech, 2022)
Make-Up that women need to maintain their appearance and self-confidence to look more attractive for themselves and when dealing with other people. The information system is an important resource that needs to be managed by a Make-Up service provider because it has a high level of accuracy in data processing. The design of this system aims to display information on available Make-Up and Make-Up service providers including prices and locations. This system uses the PHP and MySQL programming languages. The Make-Up and Make-Up service provider system is designed using the Waterfall methodology, which starts from the planning process, needs analysis, design, and implementation in the form of coding, testing/verification and maintenance. The results of this study are a Make-Up service website that is available to make it easier for customers to choose the makeup they want, in this website, Make-Up owners can visit their services on the website and are also supported by transaction features that make it easier for customers to can place an order.